Fixed template network and dynamic template network: novel network designs for decoding steady-state visual evoked potentials. (1st October 2022) - Xiao, Xiaolin; Xu, Lichao; Yue, Jin; Pan, Baizhou; Xu, Minpeng; Ming, Dong
Abstract: Objective . Decomposition methods are efficient to decode steady-state visual evoked potentials (SSVEPs). In recent years, the brain–computer interface community has also been developing deep learning networks for decoding SSVEPs. However, there is no clear evidence that current deep learning models outperform decomposition methods on the SSVEP decoding tasks. Many studies lacked the comparison with state-of-the-art decomposition methods in a fair environment. Approach . This study proposed a novel network design motivated by the works of decomposition methods. Fixed template network (FTN) and dynamic template network (DTN) are two novel networks combining the advantages of fixed templates and subject-specific templates. This study also proposed a data augmentation method for SSVEPs. This study compared the intra-subject classification performance of DTN and FTN with that of state-of-the-art decomposition methods on three public SSVEP datasets. Main results . The results show that both FTN and DTN achieved the suboptimal classification performance compared with state-of-the-art decomposition methods. Significance . Both network designs could enhance the decoding performance of SSVEPs, making them promising networks for improving the practicality of SSVEP-based applications.